Three-dimensional observation and image-based modelling of thermal strains in polycrystalline alumina - Gonzalez, D; King, A; Mostafavi, M; Reischig, P; Rolland Du Roscoat, S; Ludwig, W; Quinta Da Fonseca, J; Withers, P; Marrow, T; Marrow, T (Elsevier, 2013)
Diffraction contrast tomography (DCT) with synchrotron X-rays was used to map the three-dimensional microstructure of alumina. Each grain boundary (GB) of this coarse-grained ceramic was characterized by its orientation and the crystal misorientation of the adjacent grains. The microstructure of alumina was sufficiently well described by DCT to produce a microstructurally representative image-based finite-element model comprising ∼400 grains. Grain boundary cohesive elements were used to calculate the local thermal stresses acting on each GB arising from the crystal anisotropy. Digital volume correlation of the CT images was used to gauge the degree of bending induced during loading and to extract polycrystalline elastic properties. The model simulations showed the average intergranular stress to be influenced by the orientation of the GB plane relative to the basal planes of the adjacent grains. Boundaries to which at least one of the basal planes was closely aligned tended to develop higher tensile stress; these boundaries were predicted to have a tendency for intergranular fracture. Under compressive loading, the normal stresses of the boundaries that cracked were slight more tensile relative to the general population due to grain-to- grain interactions. The predicted effect of crystal lattice strains and rotations on diffraction, due to the modelled thermal stresses, showed general agreement with the observed X-ray diffraction images of individual grains. © 2013 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.